Antibacterial activities of TiO2 nanotubes on Porphyromonas gingivalis. Issue 43 (14th May 2015) - Shi, Xiaoguo; Xu, Quan; Tian, Ang; Tian, Yulou; Xue, Xiangxin; Sun, Hongjing; Yang, He; Dong, Chenbo
<x xml:space="preserve">Abstract</x> The potential impacts of TiO2 nanotubes on Porphyromonas gingivalis growth and drug resistance were investigated. TiO2 nanotubes antibacterial performance can be manipulated with the photocatalytic activity as well as the geometry characteristic.